Experimental Proof of the Bifunctional Mechanism for the Hydrogen Oxidation in Alkaline Media. (8th November 2017) - Li, Jingkun; Ghoshal, Shraboni; Bates, Michael K.; Miller, Todd E; Davies, Veronica; Stavitski, Eli; Attenkofer, Klaus; Mukerjee, Sanjeev; Ma, Zi‐Feng; Jia, Qingying
Abstract: Realization of the hydrogen economy relies on effective hydrogen production, storage, and utilization. The slow kinetics of hydrogen evolution and oxidation reaction (HER/HOR) in alkaline media limits many practical applications involving hydrogen generation and utilization, and how to overcome this fundamental limitation remains debatable. Here we present a kinetic study of the HOR on representative catalytic systems in alkaline media. Electrochemical measurements show that the HOR rate of Pt‐Ru/C and Ru/C systems is decoupled to their hydrogen binding energy (HBE), challenging the current prevailing HBE mechanism. The alternative bifunctional mechanism is verified by combined electrochemical and in situ spectroscopic data, which provide convincing evidence for the presence of hydroxy groups on surface Ru sites in the HOR potential region and its key role in promoting the rate‐determining Volmer step. The conclusion presents important references for design and selection of HOR catalysts.